2019
DOI: 10.3390/molecules24173170
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Octyl Gallate on Streptococcus mutans Biofilm Formation, Acidogenicity, and Gene Expression

Abstract: The accumulation of biofilm by Streptococcus mutans bacteria on hard tooth tissues leads to dental caries, which remains one of the most prevalent oral diseases. Hence, the development of new antibiofilm agents is of critical importance. The current study reports the results from testing the effectiveness of octyl gallate (C8-OG) against: (1) S. mutans biofilm formation on solid surfaces (polystyrene, glass), (2) acidogenicity, (3) and the expression of biofilm-related genes. The amount of biofilm formed by S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…Moreover, DMSO alone, used at a concentration of 0.67%, had an insignificant effect against S. mutans biofilm development relative to that of the control bacteria (p > 0.05). Interestingly, the biofilm-inhibiting concentrations of C12-LG were in a quite narrow range, reflecting a similar finding for octyl gallate, that suppressive concentrations fell into a range from 97.4 to 100.24 µM [29]. However, this inhibitory effect of C12-LG occurred at lower concentrations than those of octyl gallate, and it was markedly greater than the activity of ethyl and methyl gallates, for which previously determined suppressive concentrations were in the ranges of 2.78-3.53 and 2.99-5.43 mM, respectively [27,28].…”
Section: Antibacterial Activity Of C12-lg On S Mutanssupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, DMSO alone, used at a concentration of 0.67%, had an insignificant effect against S. mutans biofilm development relative to that of the control bacteria (p > 0.05). Interestingly, the biofilm-inhibiting concentrations of C12-LG were in a quite narrow range, reflecting a similar finding for octyl gallate, that suppressive concentrations fell into a range from 97.4 to 100.24 µM [29]. However, this inhibitory effect of C12-LG occurred at lower concentrations than those of octyl gallate, and it was markedly greater than the activity of ethyl and methyl gallates, for which previously determined suppressive concentrations were in the ranges of 2.78-3.53 and 2.99-5.43 mM, respectively [27,28].…”
Section: Antibacterial Activity Of C12-lg On S Mutanssupporting
confidence: 62%
“…Among these natural compounds, epigallocatechin-3-gallate (EGCG), a major polyphenol in green tea (Camellia sinensis), also found in many other plants, has shown inhibitory effects against Streptococcus mutans [26]. In our previous studies, other natural derivatives of alkyl gallates that have been shown to significantly suppress S. mutans biofilm formation are methyl gallate (C1-MG) and ethyl gallate (C2-EG) [27,28], and we have demonstrated that an octyl gallate derivative (C8-OG) significantly diminished biofilm formation and suppressed the associated genes expressed in S. mutans [29]. Alkyl gallates with longer alkyl chains, e.g., the derivative lauryl gallate (dodecyl gallate), have yet to be investigated for these actions on biofilm formation and its related genes in S. mutans.…”
Section: Introductionmentioning
confidence: 78%
“…Our next study will aim to discover novel and highly active natural antibacterial products, using a novel in-house bioassay guided fractionation approach [1,28,31,37] and in-silico based modeling techniques [29,[47][48][49][50] to identify natural products that exhibit antibacterial activity against S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred µL, corresponding to 5 × 10 5 CFU/mL, was added to all the wells. The plates were incubated at 37 • C for 24 h. For more details regarding the cultivation condition, see our recent publications [1,37]. Tetracycline was used as a positive control for S. mutans.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation